Trophic structure of coastal fisheries ecosystems in the Philippines - Aliño, Lualhati Lachica (Marine Science Institute, College of Science, University of the Philippines Diliman, 2010)
This dissertation utilized various fisheries databases available in the Philippines to develop the different trophic structure models presented in the study. This is partly funded by the Sandwich Program of the Deutscher Akademischer Austausch Dienst e. V. (DAAD), German Academic Exchange Service. The program financed the one-year the models at the Center for Tropical Marine Ecology, Zentrum fur Marine Tropenokologie (ZMT). The Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA) PhD Research Scholarship provided funding from June 2008 to March 2010 for the completion of the research work.. This dissertation highlights the dynamic features of tropical systems showing the importance of trophic flows, environmental and geomorphological attributes are related to understanding how these fisheries ecosystem have profound influences in their vulnerability and resilience to disturbances especially human impacts such as fisheries and pollution.